The effects of low-load resistance training combined with blood flow restriction on knee rehabilitation in middle-aged and elderly patients: A systematic review and meta-analysis - Juan Chen; Lei Wu; Chenna Li; Hao Yan (PLoS ONE, 2025)
This meta-analysis evaluates the effectiveness of low-load resistance training combined with blood flow restriction in knee rehabilitation. Methods: Randomized controlled trials investigating the effects of blood flow restriction training on knee injury rehabilitation were systematically searched in the PubMed, EBSCO, and Web of Science databases for studies published between January 2000 and May 2024. The Cochrane Risk of Bias Tool was used to assess study quality, and statistical analyses were performed using Review Manager 5.3 software. Results: (1) Compared to low-load control training, blood flow restriction training showed no significant difference in pain scores (standardized mean difference = -0.10, P = 0.46) but significantly improved muscle strength (standardized mean difference = 1.11, P < 0.00001). (2) When compared to high-intensity resistance training, blood flow restriction training demonstrated no significant differences in muscle strength (standardized mean difference = -0.11, P = 0.74) or pain scores (standardized mean difference = -0.84, P = 0.17). (3) Preoperative blood flow restriction training did not significantly improve postoperative pain scores (standardized mean difference = 0.77, P = 0.37); however, among 241 patients undergoing preoperative training, blood flow restriction training significantly enhanced postoperative muscle strength (standardized mean difference = 0.97, P = 0.03). Conclusions: Although blood flow restriction training has limited effects on reducing pain, it significantly improves muscle strength, particularly in preoperative rehabilitation and low-load training settings, making it a valuable alternative in clinical knee rehabilitation strategies.